2017
DOI: 10.1039/c7cp01787a
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the exchange coupling in linear copper porphyrin oligomers

Abstract: Linear π-conjugated porphyrin oligomers are of significant current interest due to their potential applications as molecular wires. In this study we investigate electronic communication in linear butadiyne-linked copper porphyrin oligomers by electron paramagnetic resonance (EPR) spectroscopy via measurement of the exchange interaction, J, between the copper(ii) centers. The contributions of dipolar and exchange interactions to the frozen solution continuous wave (cw) EPR spectra of the compounds with two or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 37 publications
(38 reference statements)
2
16
0
Order By: Relevance
“…By including more parameters in the simulation, such as the nitrogen couplings and the exchange coupling, the fit could most likely be improved. 43 However, the rather featureless character of the spectrum makes it difficult to assign quantitatively and confidently precise values to the different interactions, as all of these additional parameters only contribute to fielddependent line broadening in the present case. Note that similar, butadiyne-linked, compounds, 43 exhibit an exchange coupling of about 50 MHz.…”
Section: Cup2: Small Exchange Couplingmentioning
confidence: 82%
See 2 more Smart Citations
“…By including more parameters in the simulation, such as the nitrogen couplings and the exchange coupling, the fit could most likely be improved. 43 However, the rather featureless character of the spectrum makes it difficult to assign quantitatively and confidently precise values to the different interactions, as all of these additional parameters only contribute to fielddependent line broadening in the present case. Note that similar, butadiyne-linked, compounds, 43 exhibit an exchange coupling of about 50 MHz.…”
Section: Cup2: Small Exchange Couplingmentioning
confidence: 82%
“…43 However, the rather featureless character of the spectrum makes it difficult to assign quantitatively and confidently precise values to the different interactions, as all of these additional parameters only contribute to fielddependent line broadening in the present case. Note that similar, butadiyne-linked, compounds, 43 exhibit an exchange coupling of about 50 MHz. But if the two porphyrin planes of CuP2 are perpendicular to each other, consistent with X-ray and DFT studies of similar compounds, the exchange coupling is expected to be close to zero.…”
Section: Cup2: Small Exchange Couplingmentioning
confidence: 82%
See 1 more Smart Citation
“…In recent work it was demonstrated that such measurements reveal otherwise inaccessible information on the electronic structure of the systems. 16,25 Secondly, complexes of Cu(II) ions are attracting attention in bio-EPR spectroscopy, [26][27][28][29] both as native metal centres in proteins, 23,26,[30][31][32][33][34][35][36][37][38] and as spin labels for orthogonal pulse dipolar spectroscopy. 39,40 The potential of the latter approach has been recognised previously and is reflected in a growing interest in Cu(II)-based spin labelling strategies.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Significant progress in performing and analysing Cu(II)-based PDS experiments has been achieved over the past few years. [28][29][30][31][32][33] Exchange interactions are often observed for Cu(II) ions that are bound to conjugated p-systems, [34][35][36][37][38][39] or in strongly coupled systems, such as molecular magnets. 7,40,41 The exchange coupling may give additional information on the system of interest, yet, the dipolar and exchange couplings can become difficult to disentangle.…”
Section: Introductionmentioning
confidence: 99%